Spectrophotometric Determination of Acyclovir Drug via Charge-Transfer Complex Formation - Hadeel M. Dawood; Abdulsahib, Hassan T.; Atared F. Hassan (International Journal of Medical Toxicology and Legal Medicine, 2024)
An Accurate, simple, rapid, inexpensive and sensitive method has been applied for the spectrophotometric determination of acyclovir, in bulk sample and dosage form, depending on the formed charge-transfer complex between the cited drug and, 2,3-Dichloro-5,6-dicyano-p-benzoquinone (DDQ) as a chromogenic reagent. The formed complex shows absorbance maxima at 420 nm against the reagent blank. The calibration graph is linear within (1.0 - 22.0) µg.mL-1 with a detection limit of 0.60 µg.mL-1. The results show the absence of interferences from the excipients on the determination of the drug. Therefore, the proposed method has been successfully applied for the determination of acyclovir in pharmaceutical preparations.